Peer Influence as a Mediator of Present Bias and Self-Control on Risk Credit Behavior - Ella Novilia; Muhammad Sulhan (Universitas Negeri Padang, 2026)
Risk credit behavior among students has emerged as a growing concern due to increasing financial accessibility and consumption-oriented lifestyles. This study aims to analyze the effect of present bias and self-control on risk credit behavior, with peer influence as a mediating variable. This research adopted a quantitative approach involving 110 students from the Faculty of Economics at UIN Maulana Malik Ibrahim Malang and utilized PLS-SEM with SmartPLS for data analysis. The findings indicate that present bias and self-control have positive but insignificant effects on risk credit behavior, while both exert a positive and significant effects on peer influence. Peer influence also has a positive and significant effect on risk credit behavior and significantly mediated the relationship between present bias, self-control, and risk credit behavior. These findings contribute to Social Cognitive Theory by demonstrating that peer influence mediates the effects of present bias and self-control on risk credit behavior, highlighting the importance of integrating psychological and social factors in explaining students' financial behavior.